1999
DOI: 10.1046/j.1365-2915.1999.00159.x
|View full text |Cite
|
Sign up to set email alerts
|

Mass treatment with ivermectin for filariasis control in Papua New Guinea: impact on mosquito survival

Abstract: Field studies were carried out to determine the impact of mass human treatment with ivermectin on the survival of anthropophagic mosquitoes of the Anopheles punctulatus complex (Diptera: Culicidae), the vectors of lymphatic filariasis and malaria in Papua New Guinea. In a village where mass treatment had been given, using 400 microg/kg ivermectin plus 6 mg/kg diethylcarbamazine citrate (DEC), we performed pre- and post-treatment collections of freshly blood-engorged mosquitoes from the same nine bedrooms. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 9 publications
0
43
0
Order By: Relevance
“…Mass treatment of IVM for filariasis control in Papua New Guinea produced blood levels that were toxic to mosquitoes of the An. punctulatus group (Bockarie et al 1999). Studies by Pampiglione et al (1985) that compared between three mosquito species found the insecticidal effect of IVM to be greater against anophelines than culicines.…”
Section: Discussionmentioning
confidence: 96%
“…Mass treatment of IVM for filariasis control in Papua New Guinea produced blood levels that were toxic to mosquitoes of the An. punctulatus group (Bockarie et al 1999). Studies by Pampiglione et al (1985) that compared between three mosquito species found the insecticidal effect of IVM to be greater against anophelines than culicines.…”
Section: Discussionmentioning
confidence: 96%
“…The literature varies on the longevity of the insecticidal effect, with some finding a prolonged effect [10]. The effects of ivermectin on blood-sucking insects and parasites may be only loosely related to plasma concentration, possibly because of metabolites with longer half-lives [11,12]. Data on the pharmacokinetics of ivermectin in humans vary.…”
mentioning
confidence: 97%
“…Experiments in animals and in vitro have shown that ivermectin readily kills adult mosquitoes, including anophelines [8,9]. In human trials of mass drug administration for onchocerciasis and filariasis, the effect of ivermectin on mosquitoes seems to be maintained in the field [10,11]. These insecticidal properties of ivermectin have led some to suggest that this drug could have a role in the control of arthropod vector-borne diseases.…”
mentioning
confidence: 98%
“…5 Light traps are commonly used for the collection of mosquitoes for LF xenomonitoring, [6][7][8] and are usually placed indoors near a sleeping person who is protected with an untreated mosquito net. Other methods such as human landing catches have been used, 9 but this method is used less often due to ethical concerns. 10 Gravid traps have been used for the collection of mosquitoes for xenomonitoring, particularly in the United States for monitoring of Western Equine, St. Louis, and West Nile viruses.…”
Section: Introductionmentioning
confidence: 99%